Outage performance analysis of full-duplex assisted non-orthogonal multiple access with bidirectional relaying mode. (27th April 2021) - Nguyen, Thanh-Luan; Do, Dinh-Thuan
The fifth-generation (5G) wireless network needs massive connectivity to allow large number of users access to network in the same time. Non-orthogonal multiple access (NOMA) and full-duplex (FD) are two promising techniques recommended for the 5G wireless network. This work combines these approaches to improve system outage performance in the situation of bidirectional cooperative relaying. The main metric to evaluate system performance relying on outage probability. Notably, the outage expression for such a system under the Nakagami- m fading environment is derived for exact and approximate computation. The simulation results demonstrated the effectiveness of NOMA and FD in low transmit power compared to conventional half-duplex (HD) and orthogonal multiple access (OMA) schemes.